Descending Cephalic to Epigastric Sensation in a Patient with Mesial Temporal Lobe Epilepsy: A Novel Observation - Sureshbabu, Sachin; Joseph, Merisin; K. G, Sruthi; Mohanlal, Smilu; Peter, Sudhir; Chindripu, Sobhana; Janardhanan, Sujith; Karunanithi, Sellam; T.K, Sreekumar; Basheer, Noufal; Alappat, Jacob P. (International Journal of Epilepsy, 2021)
One of the most frequent type of auras in mesial temporal lobe epilepsy (MTLE) is epigastric sensation. Until now the site of the symptomatogenic zone of the epigastric aura remains controversial. The temporal lobe as well as insular cortex has been implicated. Our case is that of a 29-year-old young woman patient who presented with an aura of descending cephalic to epigastric sensation as opposed to the prototypical ascending aura. Interictal and ictal recording favored a mesial temporal pattern. Magnetic resonance imaging brain showed left mesial temporal lobe sclerosis. Interictal positron emission tomography showed concordant findings. The patient underwent selective amygdalohippocampectomy following which she remains seizure-free. This previously unreported clinical expression of MTLE and its origins is discussed.
Keywords: epilepsy; epigastric aura; mesial temporal lobe epilepsy